"I thought this is like magic": a discursive study on the ways patients marginalise homeopathy in talk. Issue 2 (6th October 2017) - Campbell, Craig; Futak-Campbell, Beatrix
Abstract : This study applies an eclectic discourse analysis within a poststructuralist framework to data consisting of research interviews with 17 patients attending National Health Service (NHS) clinics for homeopathic treatment in the UK. This combined approach focuses on the fine-grain action orientation of language use while investigating notions of power, subjectivity and discourse. Homeopathic patients' spontaneous discursive resources demonstrate how broader available discourses of homeopathy are used to negotiate, legitimise and sustain their healthcare choices. In particular, patients orient to three discursive strategies: (1) describing the failures of medicine, to warrant the turn to seek homeopathy; (2) emphasising the extraordinary, curative properties of homeopathy; and (3) constructing homeopathy as an alternative with considerable health benefits. The study shows how these intersubjective constructions are mobilised as social action to perform convincing arguments and at the same time manage and attend to subjects' own individual personal credibility. Despite all their positive intentions, these strategies end up locating homeopathy in a culture of scepticism and marginalising it from mainstream acceptance.